Integrasi Digital Storytelling Berbasis Nilai Moderasi Beragama dalam Pembelajaran Sejarah Kebudayaan Islam di Madrasah Ibtidaiyah - Ernawati Ernawati; Baiq Ida Astini; Hijratul Hasri; Indra Mayadi; Israfatul Ilmi (Najah Bestari, 2026)
This study aims to analyse the integration of digital storytelling based on the value of religious moderation in the teaching of Islamic Culture Studies (SKI) at Madrasah Ibtidaiyah, using a Systematic Literature Review (SLR) approach. Literature sources were collected from Google Scholar, Scispace, DOAJ and Scopus databases, with publication criteria between 2016 and 2026. The results of the study show that digital storytelling significantly contributes to improving concept understanding, learning engagement, and experiential learning through the presentation of digital narrative-based material. Integrating values of religious moderation into SKI education plays a crucial role in fostering tolerance, empathy, and an inclusive religious character among students. This approach not only serves as a learning medium, but also as a pedagogical strategy that is relevant to the needs of Islamic education in the digital era. These findings emphasise the importance of contextual and value-based content design, enhancing teachers' digital competencies, and institutional support in optimally implementing digital storytelling in Madrasah Ibtidaiyah.